To express g(x) as a transformation of f(x), we can see that g(x) is obtained by multiplying each y-coordinate of f(x) by 0.5.
Therefore, the transformation from f(x) to g(x) can be expressed as:
g(x) = 0.5 * f(x)
Applying this transformation to f(x) = (1,4); (4,8), we get:
g(x) = (0.5 * 1, 0.5 * 4); (0.5 * 4, 0.5 * 8)
g(x) = (0.5, 2); (2, 4)
Thus, g(x) can be expressed as a transformation of f(x) by multiplying each y-coordinate of f(x) by 0.5.
points g(x) = (1,2); (4,4)
f(x) = (1,4); (4,8)
how can g(x) be expressed as a transformation of f(x)?
1 answer